Perspectives for Surrogate Safety Studies in East-European Countries - Rasa Ušpalytė-Vitkūnienė; Aliaksei Laureshyn (The Baltic Journal of Road and Bridge Engineering)
The road safety development in East-European countries follows in general the trends of the western countries, even though there is a time lag. The fatality numbers are decreasing, though the improvements for the vulnerable road users are less impressive compared to other road user categories. The traditional road safety analysis based on accident history has many limitations related to accident under-reporting, low and random accident counts at individual sites and lack of details in the police or hospital reports. The surrogate safety methods are based on observation of other-than-accident occurrences that still have a strong relation to safety in traffic. Such methods are often more efficient (and pro-active) for safety assessments. The paper reviews the current status of the surrogate safety analysis methods, the challenges, and opportunities related to modern urban traffic conditions and the emerging technologies for more efficient data collection. The method is put in the context of the East-European countries to see how it contribute to the on-going road safety work and a better understanding of accidents risk factors necessary for producing effective safety countermeasures.